Odpowiedź:
Szczegółowe wyjaśnienie:
a) 2x+3/5 = 2-x /3 - x / × 15
30x + 9 = 30 - 5x - 15x
30x + 5x + 15x = 30 - 9
50x = 21 / 50
x = [tex]\frac{21}{50}[/tex]
b) x+1/2 - x-1 /3 = 1/4
[tex]\frac{1}{2\\}[/tex] - [tex]\frac{1}{3}[/tex] = [tex]\frac{1}{4}[/tex]
[tex]\frac{1}{6}[/tex] = [tex]\frac{1}{4}[/tex]
x ⊂ ∅
c) 4x + 7/2 - 5x-1 /6 = x+5
4x - 5x - x = 5 + 1/6 - 7/2
- 2x = 5/1 + 1/6 - 21/6
-2x = 30/6 + 1/6 - 21/6
-2x = [tex]\frac{30 + 1 - 21}{6}[/tex]
-2x = 10/6 / -2x
x = - 5/6
d) x+5 /4 - 2x+1 /8 = 1/2 (2-x)
-x +11/8 = 1 - 1/2x /× 8
-8x + 11 = 8-4x
-8x + 4x = 8-11
-4x = -3 /-4
x = 3/4